Impressions of the first most complete authorand tafsir in the Nusantara ( Analysis Study of the Book of Tarjuman Al-Mustafid ) - Rumi Chafidzoh, Rumi Chafidzoh; Salamah Noorhidayati, Salamah Noorhidayati; Abdul Rahim, Mohd Hisyam (2024)
The book of Tarjuman al-Mustafid is the first complete tafsir book of 30 juz in the nusantara in the 17th century AD. This article focuses research on the first and last suras in the Qur'an, namely suras al-Fatihah and al-Nas to get an impression from sheikh Abd ar-Rauf as-Sinkili in writing a complete Qur'anic tafseer of 30 juz. This interpretation shows evidence of the extraordinary productivity of tafsir writing in the archipelago at the beginning of the process of Islamization in Indonesia. Descriptive and qualitative approach, this research is needed to get results that are in accordance with existing facts and reality. The uniqueness of 'Abd al-Rauf's tafsir, can be seen from his impression in writing tafsir, where he is very maintaining the consistof enan from the beginning to the end of the letter in the technique of writing tafsir, there are several keywords which is used repeatedly to interpret. This is a characteristic that other books of exegesis do not have. But during the final process of interpreting the meaning of the verse, an impression of inconsistent interpretation was found